Evaluation of Reward and Punishment Methods in Improving Student Discipline at SDN 39 Palembang - Ananda Irma Utami; Dela Dela; Fatiyah Ummul Izzah; Tri Mayang Sari; Siti Aisyaturrodiyah (Journal on Education, 2023)
Education plays a vital role in the development of a nation. A teacher is expected to determine the right teaching approach in the teaching and learning process. One strategy that can increase attention and make students more active is to reward rewards, praise, and punishment. This type of research is qualitative descriptive research. The subjects in this study were the principal, Waka students, class teachers, and students at SDN 39 Palembang. The research results proved that the assessment of reward and punishment methods on student discipline at SDN 39 Palembang was considered good. Therefore, the reward and punishment method can motivate student enthusiasm and increase student discipline at school.